1991
DOI: 10.1017/s0022112091003713
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of swimming three-dimensional waving plates

Abstract: The three-dimensional waving plate theory is developed to investigate the swimming performance of fish undulatory motion. In particular, the propulsive effectiveness is discussed. The unsteady potential flow over model rectangular and triangular flexible plates performing a motion which consists of a progressing wave with variable amplitudes is calculated by the vortex ring panel method. It is found that the undulatory motion can reduce three-dimensional effects. It is this important hydrodynamic phenomenon th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(72 citation statements)
references
References 10 publications
5
67
0
Order By: Relevance
“…According to the 3D £exible plate model of ¢sh swimming (Cheng et al 1991), the total thrust due to pressure di¡erences on the plate, the hydrodynamic power to maintain the movement of the plate in water, and the lateral force can be derived, and their coe¤cients can be written as Figure 11. The time-courses of the onset and end of EMG activity on the left side of a swimming mackerel or saithe (Wardle & Videler 1993), and of the muscle bending moment (M m ) along the body length calculated by the present theory for saithe.…”
Section: (C) Body Bending and Hydrodynamic Propulsionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the 3D £exible plate model of ¢sh swimming (Cheng et al 1991), the total thrust due to pressure di¡erences on the plate, the hydrodynamic power to maintain the movement of the plate in water, and the lateral force can be derived, and their coe¤cients can be written as Figure 11. The time-courses of the onset and end of EMG activity on the left side of a swimming mackerel or saithe (Wardle & Videler 1993), and of the muscle bending moment (M m ) along the body length calculated by the present theory for saithe.…”
Section: (C) Body Bending and Hydrodynamic Propulsionmentioning
confidence: 99%
“…As in almost all studies of ¢sh hydrodynamics (Lighthill 1960(Lighthill , 1971(Lighthill , 1975Wu 1971a;Cheng et al 1991), we conceptually separate the production of thrust, by the essentially non-viscous reaction of the water to lateral movements of the body, from the countervailing drag generated by longitudinal inertia (mass Âacceleration), so if we can use the observed motions to calculate the thrust and longitudinal acceleration, we can infer the drag. However, in this paper we are concerned not with the overall thrust and drag but with the time-varying distribution of lateral forces along the body, because it is these that are generated by the bending of the body and that contribute to the distribution of bending moment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classical works by Taylor (Taylor, 1952) and Lighthill (Lighthill, 1960;Lighthill, 1969;Lighthill, 1970;Lighthill, 1971) and their extensions (Cheng et al, 1991) provide analytical models of fluid forces acting on the body during undulatory swimming. The fluid forces were modeled as static functions of kinematic variables: velocity-dependent resistive force (Taylor, 1952) for low Reynolds number (Re) swimming or acceleration-dependent reactive force (Lighthill, 1960) for high Re swimming.…”
Section: Introductionmentioning
confidence: 99%
“…The finding is supported by the experiments on oscillating foils [3][4][5] . However, such theoretical analyses made by Lighthill [1,2,6] , Wu [7] , Newman [8] , and Cheng et al [9] are limited to inviscid flows. In some recent experimental and numerical studies [10][11][12][13][14][15][16] , the propulsive efficiency is found to be related to the wiggling frequency and wavelength, and the vortex structure is related to the propulsive performance.…”
Section: Introductionmentioning
confidence: 99%